Nanocomposites of carbon nanomaterials and metallophthalocyanines : applications towards electrocatalysis - Nyoni, Stephen (Rhodes University, Faculty of Science, Department of Chemistry, 2016)
Nanohybrid materials have been prepared and examined for their electrocatalytic activity. The nanocomposites have been prepared from carbon nanomaterials (multiwalled carbon nanotubes (MWCNTs) and graphene nanosheets), cadmium selenide quantum dots and metallophthalocyanines (MPcs). The MPcs used in this work are cobalt tetraamino-phthalocyanine (CoTAPc) and tetra (4-(4,6-diaminopyrimidin-2-ylthio) phthalocyaninatocobalt (II)) (CoPyPc). Their activity has also been explored in different forms; polymeric MPcs, iodine doped MPcs and covalently linked MPcs. The premixed drop-dry, sequential drop-dry and electropolymerisation electrode modification techniques were used to prepare nanocomposite catalysts on the glassy carbon electrode (GCE) surface. The sequential drop dry technique for MPc and MWCNTs gave better catalytic responses in terms of limit of detection, catalytic and electron transfer rate constants relative to the premixed. MWCNTs and CdSe-QDs have been used as intercalating agents to reduce restacking of graphene nanosheets during nanocomposite preparation. Voltammetry, chronoamperometry, scanning electrochemical microscopy and electrochemical impedance spectroscopy methods are used for electrochemical characterization modified GCE. X-ray photoelectron spectroscopy, X-ray diffractometry, transmission electron microscopy, scanning electron microscopy, infra-red spectroscopy, Raman spectroscopy were used to explore surface functionalities, morphology and topography of the nanocomposites. Electrocatalytic activity and possible applications of the modified electrodes were tested using oxygen reduction reaction, l-cysteine oxidation and paraquat reduction. Activity of nanocomposites was found superior over individual nanomaterials in these applications.
Keywords: Nanocomposites (Materials); Nanostructured materials; Electrocatalysis